Communities and old regime in a traditional area of Peru - Plasencia Soto, Rommel (2019)
Conflict between huancavelican peasants, the landlords and power networks; rescued from local archives, offer the opportunity to verify that the socio-ethnics indicators were important and are offered as a gap through which we observe. However, the Andean peasants never lowered their heads where important that are revealed as significant in the social dynamics of rural Perú.